2004
DOI: 10.1902/jop.2004.75.9.1203
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Levels of Interleukin‐1β and Glycemic Control in Patients With Chronic Periodontitis and Type 2 Diabetes

Abstract: Poor glycemic control is associated with elevated GCF IL-1beta. These data are consistent with the hypothesis that hyperglycemia contributes to an heightened inflammatory response, and suggests a mechanism to account for the association between poor glycemic control and periodontal destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
121
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 39 publications
11
121
1
9
Order By: Relevance
“…There is considerable evidence that diabetes enhances the innate immune response in the periodontium. IL-1beta, TNF-alpha and the chemokine MCP-1 are elevated in the gingival crevicular fluid or serum of diabetic patients and are correlated with increased periodontal tissue destruction (69)(70)(71)(72). Monocytes from patients with type 1 diabetes produce significantly greater amounts of TNF-alpha, IL-1beta and PGE2 in response to LPS compared to matched normoglycemic individuals (72,73).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…There is considerable evidence that diabetes enhances the innate immune response in the periodontium. IL-1beta, TNF-alpha and the chemokine MCP-1 are elevated in the gingival crevicular fluid or serum of diabetic patients and are correlated with increased periodontal tissue destruction (69)(70)(71)(72). Monocytes from patients with type 1 diabetes produce significantly greater amounts of TNF-alpha, IL-1beta and PGE2 in response to LPS compared to matched normoglycemic individuals (72,73).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Causes for periodontal diseases are known to be various factors, dental occurrence of periodontal disease is higher and accelerates resorption of alveolar bone, and inadequate control of blood sugar level was related to the severity of periodontal diseases [13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…AGE alter the immune response in T2D with up‐regulation of pro‐inflammatory cytokines, e.g., Tumor Necrosis Factor‐α (TNF‐α) (Ramasamy, Yan, & Schmidt, 2012), which in turn is believed to influence the progression of PD (Lalla & Papapanou, 2011). Furthermore, T2D affects the oral environment with higher glucose levels and pro‐inflammatory mediators in the gingival crevicular fluid, which have been regarded key mechanisms for modifying the microbiota in T2D patients (Engebretson et al, 2004; Ficara, Levin, Grower, & Kramer, 1975). Recent studies have demonstrated different bacterial profiles of subgingival plaque in T2D patients with chronic PD as compared to PD patients without T2D (Casarin et al, 2013; Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%